Interactive Multimedia In Shallow Foundation Support Capacity Material on S1 PTB FT UNJ - Arthur, Riyan; Septiandini, Erna; Renna, Nousseva (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is to produce a product in the form of Interactive Multimedia on the material shallow bearing capacity of soil in the Building Engineering Education Study Program, University of Jakarta. The method of this research is research and development (R&D) method with the ADDIE model consisting of the stages of analysis, design, develop, implement, and evaluation. The interactive multimedia that was developed got 80.7% with the proper category by material experts and 79.4% with the proper category by media experts. Based on the results of the limited trial, there was an increase in the average value of the pre test by 54.5 and the post test by 79.75. The results of validation by material experts and media experts as well as limited trials show that interactive multimedia that has been developed is declared feasible and ready to be implemented in the material foundation bearing capacity of soil.